Intervention to Prevent Mental Ill-Health Among Health Care Workers - Michélsen, Hans; Sebrant, Ulla; Schulman, Abbe (Nordic Journal of Working Life Studies, 2014)
Psychological strain in working life is gaining ever more attention. Health care workers are often under extreme emotional stress, which can become so overwhelming that they show signs of mental ill-health. This project aimed to develop a model for sustainable psychological support within a hospital clinic to prevent mental ill-health among employees. Mental strains at work and mental ill-health among clinic employees were mapped out, after which interventions for psychological support were designed in collaboration with employees. The interventions were conducted over one year and evaluated. Throughout the process the clinic received continuous feedback. Both questionnaires and interviews were used. The results of identifying mental strains and conducting interventions showed that employees experienced mental strain at work and perceived a need for support. Intervention evaluations showed that the project provided support, new insights, and an increased acceptance for long-term prevention of mental strain. Quantitative and qualitative methodologies supported the results. The conclusion was that increased legitimacy for mental strain at work and continuous feedback between clinic management and employees, as well as organizational circumstances are important factors when developing long-term intervention programs with various forms of psychological support.